Taxonomic studies on the genus Delphinium (Ranunculaceae) from China (XXIII): Reduction of D. conaense to the synonymy of D. bhutanicum, a species newly reported for China - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2023)
Based on critical observations on herbarium specimens (including type material) and living plants in the wild, we demonstrate that Delphinium bhutanicum (Ranunculaceae), previously recorded only from Bhutan, is distributed also in southern Xizang (Tibet), China. We also determine that D. conaense, described from Cona in southern Xizang, is conspecific with D. bhutanicum. We therefore report D. bhutanicum as a newly recorded species for China and place D. conaense in synonymy with it herein.